PENYALAHGUNAAN PEMBERIAN KUASA UNTUK MENJUAL DALAM PERJANJIAN PENGIKATAN JUAL BELI (PPJB) OLEH PENERIMA KUASA (CONTOH KASUS : PUTUSAN MAHKAMAH AGUNG NOMOR 1846/K/PDT/2017) - Livia Cindy Ariella; Endang Pandamdari (Jurnal Hukum Adigama, 2019)
A sale and purchase agreement is one of the most frequently made agreements. One of the most traded objects is land. According to customary law, land sale and purchase is a legal act of transferring land rights. The legal act of sale and purchase is carried out by a land deed official who has the authority to make a sale and purchase deed. Sometimes, the sale and purchase deed cannot be made because there are conditions that have not been fulfilled, so the parties first make a preliminary agreement called the binding sale and purchase agreement. Usually, the binding sale and purchase agreement is followed by power of attorney to sell. The formulation of the problem in this thesis is whether the inclusion of the power of attorney to sell is permissible, and if the recipient of the power of attorney misuses the power, what form of legal protection can be given to the authorizer. The author uses normative legal research methods that are supported by interviews to answer these problems. The inclusion of a power of attorney to sell within the binding sale and purchase agreement is permitted as long as it is not an absolute power that is prohibited by law. Legal protection that can be given to the authorizer is divided into two forms: preventive protection, a legal protection aimed at preventing the occurrence of disputes, and repressive protection, a protection that serves to resolve in the event of a dispute.